Obciążenia ludności podatkami lokalnymi: Population burden local taxes - Szarek, Stanisław; Gołocka, Renata (Management and Administration Journal, 2021)
It was examined the tax burden per capita of local taxes in 2008-2012 in Repki community. It was found that nominal and real local tax burden per 1 inhabitant in the investigation period clearly increased.